EDUKASI MYOB ACCOUNTING PADA SMKN 2 MANDAU - Lubis, Nurhayani; Hardi; Nofrizal; Maryanti, Sri; Siregar, Inova Fitri (Komunitas Manajemen Kompetitif, 2025)
MYOB accounting is software designed for financial accounting purposes, facilitating the recording of an organization's financial transactions. This application provides real-time financial data and has a user-friendly interface. According to the directives of the Ministry of National Education (Kemendiknas) in 2010, schools, particularly vocational high schools (SMK), are required to assess accounting competencies using the Mind Your Own Business software. SMKN 2 Mandau is a vocational school located in Bathin Solapan District, precisely at the border between Duri and Dumai, Riau Province. The school has one accounting class for each grade. As with other vocational schools, the curriculum of this school includes material on accounting software. Discussions with the head of the accounting laboratory and the curriculum coordinator at SMKN 2 revealed that students' ability to operate the MYOB accounting system is still limited. This community service involves three methods: preparation, implementation, and evaluation stages. The service was carried out on July 31, 2024. The results from the questionnaire distributed before the training indicate that students' understanding and awareness of MYOB Accounting were relatively low. Of the five statements in the questionnaire, statements 1 through 4 all received results below 50%. The results from the questionnaire after the MYOB Accounting training at SMKN 2 Mandau showed that the training significantly improved students' knowledge and skills. The average score for all statements increased to above 60%, with the highest improvement being in awareness and actual experience of the benefits of MYOB Accounting education, which rose to 74%.